Between rhetoric and reality physicians and implementation of quality management in healthcare service - Abd. Manaf, Noor Hazilah (Malaysian Institute of Management, 2007)
Quality management plays a central role in healthcare services today as policy-makers and healthcare managers search for the panacea for cost containment and error reduction in the delivery of healthcare services. While the rhetoric speaks volumes of the capacity of quality improvement tools and techniques, the reality may paint a different picture among the physicians. A survey on public hospitals in Peninsular Malaysia shows that while there is good practice of quality management among employees of hospitals under the Ministry of Health (MOH), the physicians, however, are found to be lagging behind. Perception of practice of quality management was found to be lower among physicians in comparison to other employees. Physician were also found to have lower perception implementation outcome of quality management compared to other groups of employees. This paper also highlights and recommends the need for greater involvement of physicians in quality improvement activities and the use of 'opinion leaders' to influence physician practice.